A Raman metrology approach to quality control of 2D MoS2 film fabrication. (5th April 2017) - Mercado, Elisha; Goodyear, Andy; Moffat, Jonathan; Cooke, Mike; Sundaram, Ravi S
Abstract: Promising electronic and optoelectronic properties of two-dimensional (2D) materials have spurred research into large area fabrication through vapour deposition and etching. However, robust and efficient non destructive characterization techniques are required in order to reliably produce good quality uniform layers. Here, we present a Raman spectroscopy approach for characterization of the quality and a systematic study of the impact of process parameters for the production of 2D MoS2 layers. We also present the application of this characterization technique for controlled layer by layer etching of multilayer MoS2 .